GAMBARAN MATERI PEMBELAJARAN DI SURAU CANGKIANG DUSUN SIKAPAK USANG DESA TUNGKAL SELATAN KECAMATAN PARIAMAN UTARA KOTA PARIAMAN - Pertiwi, Nada Putri (Universitas Nusa Cendana, 2022)
This research is motivated by the large number of learning residents who follow the learning process at Cangkiang Surau, which is suspected to be the learning materials provided by the educators according to their needs. This study aims to describe learning materials for religion, Arabic, and art in Surau Cangkiang Dusun Sikapak Usang Desa Tungkal Selatan Kecamatan Pariaman UtarA Pariaman City.